Pendidikan Agama Kristen: Mengintegrasikan Nilai-Nilai Spiritual dalam Era Globalisasi (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The era of globalization presents serious challenges for Christian Religious Education (PAK) through the currents of value relativism, consumerism, and digital influences that threaten the formation of the spiritual character of the younger generation. This study aims to analyze strategies for integrating spiritual values ​​into Christian Religious Education (PAK) to ensure its relevance and effectiveness in facing the dynamics of the times, with a focus on a holistic approach that combines a contextual curriculum, hybrid learning media, faith-based digital literacy, and strengthening teacher competencies. The research method uses a qualitative descriptive approach based on library research through thematic content analysis of books, scientific journals, and related literature. The results indicate that effective integration of spiritual values ​​through strategies such as interactive digital learning, school-church-family collaboration, and systematic evaluation produces students who are strong in faith, critical of global influences, and ethical in character. In conclusion, the need for ongoing synergy to shape a generation of Christians who are adaptive and imbued with integrity in the era of globalization is emphasized.